Protective effects of Nigella sativa against 7,12-dimethylbenz [á] anthracene (DMBA) induced carcinogenesis in rats - Nur Fatmi Alisah; Hanif Nasiatul Baroroh; Heny Ekowati (Universa Medicina, 2012)
BackgroundLiver cancer is the third most common cause of death from cancer worldwide. Recently, natural products have been widely used as an alternative therapy for liver cancer. Previous studies have reported that Nigella sativa has chemopreventive activity in vitro and in vivo. The objective of this study was to evaluate the effect of a chloroform extract of Nigella sativa seeds (NSS) on female rat hepatocytes after administration of 7,12-dimethylbenz [á] anthracene (DMBA). MethodsThe experimental design comprised five groups of rats. Group I (DBMA control group) received oral DMBA at a dosage of 20 mg/kgBW twice weekly for five weeks, while group V (solvent control group) was given corn oil only. The other three groups received DMBA + NSS at dosages of 250 mg/kgBW, 500 mg/kgBW, and 750 mg/kgBW, respectively. Each group consisted 12 rats. The NSS extract dissolved in corn oil was administered daily by the oral route for 2 weeks before and subsequenyly during DMBA tumor induction. At the end of the study, rat livers were collected and stained with hematoxylin and eosin (H&E) and silver staining by the the AgNOR method. ResultsThere was a difference in liver tissue histopathological profile between the NSS, DMBA control, and the solvent control group. AgNOR counts in the DMBA control group, the DMBA+NSS 250 mg/kgBW group, DMBA+NSS 500 mg/kgBW group, and DMBA+NSS 750 mg/kgBW group were 1.79, 1.51, 1.41, and 1.35, respectively. ConclusionNigella sativa seed extract was able to reduce the liver damage and proliferation in rats induced by DMBA administration.